Safety Analysis of Salvage Surgery for Advanced Stages or Metastatic Lung Cancers - Bertolaccini, Luca; Galetta, Domenico; Sedda, Giulia; de Marinis, Filippo; Spaggiari, Lorenzo (The Thoracic and Cardiovascular Surgeon, 2021)
This case series aimed to analyze the outcomes of patients referred for salvage pulmonary resections after treatment with chemotherapy and immunotherapy for previously metastatic or unresectable tumors.From October 2016, after multidisciplinary board discussion, eight patients (median: 67 years, range: 52–78 years) underwent medical treatment due to advanced-stage diseases (stage cIIIA–cIVa). Four patients underwent cisplatin-based chemotherapy and, due to progression, were moved to an immunotherapy second line (nivolumab: two patients and pembrolizumab: two patients). Instead, four patients underwent combined cisplatin-based chemotherapy and immune checkpoint inhibitors (atezolizumab: two patients and pembrolizumab: two patients). After a multidisciplinary evaluation for salvage surgery, six patients underwent lobectomies, one patient underwent left pneumonectomy, and one patient underwent upper right lobectomy enlarged to the posterior arches of four ribs. The median duration of surgery was 179 minutes (range: 122–246 minutes). At the final pathological stage, three patients showed a complete major response (ypT0 ypN0), one patient was ypT1a ypN0, one ypT3 ypN0, 2 ypT3 ypN1, and one ypT4 ypN0. The hospital length of stay was 6 days (range: 3–23 days). Two patients had a postoperative complication. At the time of follow-up (median: 15.3 months [range: 1–32 months]), six patients were alive without evidence of the recurrence. Two patients died due to recurrence progression (N3 lymph nodes involvement) of the disease after 6 and 32 months.In stage IIIB–IVA nonsmall cell lung cancer, salvage lung surgeries after chemotherapy and immunotherapy are feasible, with high rates of R0 resection. Surgery can be technically tricky without significant morbidity and encouraging outcomes (even with a short-interval follow-up).
Keywords: surgery; medical treatment; lung cancer; postoperative complication; immunotherapy